Causes and Consequences of Jaundice in Pregnancy (Journal of Fatima Jinnah Medical University, 2018)
Background: Jaundice in pregnancy is an alarming condition not only for the woman but also for healthcare providers. The major causes are viral hepatitis and hypertensive diseases of pregnancy. These causes are preventable and can be controlled respectively with proper antenatal counseling and management. Objective: To determine causes and fetomaternal outcomes in pregnancies with jaundice. Design: Observational study Setting: Sir Ganga Ram hospital, Lahore. Pakistan. Duration: From January 2008 to December 2015 Method: All pregnant women presenting with jaundice in pregnancy were enrolled in the study. The causes, maternal mortality, medical and obstetrical complications and fetal outcomes were noted. Data was collected on pretested Proforma. Results: Data of 252 patients was collected and analyzed. The major cause of jaundice was viral hepatitis (74%) and out of these 66% were due to hepatitis E virus. Maternal mortality (33%) and fulminant hepatic failure (7%) were more common in this group. The second most common cause was hypertensive diseases of pregnancy (18%) and maternal mortality in this group was 17%. Obstetrical complications noted in patients with hepatitis E were: Antepartum haemorrhage (5.4%), postpartum haemorrhage (24%), preterm delivery (63%) and IUFD (28%).Medical complications observed in this group were: DIC (22%), sepsis (11%), gastrointestinal haemorrhage (4.5%). Acute fatty liver of pregnancy was diagnosed in three patients. One patient had cholestasis of pregnancy and one had malignant tumor of the liver. Conclusion: Pregnant women with jaundice and especially acute viral hepatitis by HEV infection had high maternal mortality and worse medical, obstetrical and fetal outcomes
Keywords: Jaundice, pregnancy, hepatitis